Pengaruh Metode Mind Mapping Terhadap Motivasi Belajar Siswa Pendidikan Agama Kristen kelas XI SMK Negeri 1 Siatas Barita - Devi Ani Aritonang; Oktober Tua Aritonang; Hanna Dewi Aritonang; Damayanti Nababan; Sandy Ariawan (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
The purpose of this research is to determine the positive and significant influence of the Mind Mapping Method on the learning motivation of class XI Christian religious education students at SMK Negeri 1 Siatas Barita. Tony Buzan's theory suggests that the Mind Mapping Method is a learning method that uses a note-taking strategy using keywords, image symbols, sounds, shapes and feelings. The method used in this research is a quantitative research method and the type of research is pre-experimental design in the form of